Investigation on flow visualization of beetle mimicking ornithopter - Legowo, Ari; Mohamad, Zahratu Hilall (2014)
A scale up model of beetle mimicking ornithopter, an autonomous flapping-wing micro air vehicle (MAV) is developed emulating an established model. The ornithopter model used for this purpose is developed by a team from Department of Aerospace and Information Engineering, Department of Advanced Technology Fusion and National Research Laboratory for Biomimetics and Intelligent Microsystems of the Konkuk University, Korea. We scale up the model double its original size of length 128 mm. In reality, initial design of an ornithopter is not from a certain pre-set specifications as it depends on weight, duration of battery, stability and material. The design is based on trial and error with an approach of not knowing the characteristics and performance of the wing mechanism beforehand. The wing morphology of the beetle is studied for identifying the size and weight of the model. The development of the scale up flapping wing is intended for the study of the flow visualization in a low speed wind tunnel experiment. The preliminary study on the flow visualization of the ornithopter showed some interesting patterns. Although the flow patterns are not the best of quality, however, one can see that the ornithopter generates vortices as it flaps its wing in the upstroke motion as well as in the downstroke motion. These study from the wind tunnel test will be investigated and evaluated to give some preliminary idea on the flow patterns of the ornithopter for simulating necessary aircraft load to validate the ornithopter performance in the future works.